Control strategies to alleviate dynamic loads of wind turbine system - Chua, Liza Wan Yuan. (2013)
With the depletion of fossil fuel as the main non-renewable energy resource, and growing concern on the environmental issues, trends are growing towards renewable energies, with wind energy emerging as the fastest growing renewable energy sources in the world. Wind turbine control is necessary to maximise the useful life of the wind turbine by reducing the damage to the wind turbine caused by fatigue, and regulating generator power in high wind speed operating regions preventing overheating of the generator.